2021
DOI: 10.3390/mps4010015
|View full text |Cite
|
Sign up to set email alerts
|

Total Face Approach (TFA): A Novel 3D Approach to Describe the Main Cephalometric Craniomaxillofacial Parameters

Abstract: The aim of this study is to propose a 3D skeletal classification and relative normal values of reference. Method: from a pool of 271 cone-beam computerized tomography images 108 chin-summit examinations of the skull were selected and divided into 3 traditional skeletal classes. The same Cone-beam Computerized Tomography (CBCT) images were then assessed using the cephalometric multiplanar analysis following the total face approach protocol. Results: the results of this study indicate standard 3D cephalometric n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…TFA 3D cephalometry allows the clinician to locate where the major or minor skeletal discrepancies are located with respect to ideal parameters and is also useful in the classification of the patient which helps to determine whether there is a class I skeletal intermaxillary relation [9]. The superimposition method is highly intuitive but does not provide information on the quantity and location of osteotomic movement.…”
Section: Discussionmentioning
confidence: 99%
“…TFA 3D cephalometry allows the clinician to locate where the major or minor skeletal discrepancies are located with respect to ideal parameters and is also useful in the classification of the patient which helps to determine whether there is a class I skeletal intermaxillary relation [9]. The superimposition method is highly intuitive but does not provide information on the quantity and location of osteotomic movement.…”
Section: Discussionmentioning
confidence: 99%
“…Before tracing, the CBCT images were orientated according to three reference planes identified by selecting three points on the most external slice of the CBCT scan, respectively, for every single view (coronal, axial, and sagittal), as previously done by Perrotti et al [ 6 ] ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Farronato et al [ 1 ] concluded that the information provided by the graphical representation facilitated orthodontic diagnosis making it more reliable and repeatable. Perrotti et al [ 6 ] proposed a novel 3D cephalometric analysis with relative normal values of reference.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of multiple combination medications shows that the quadruple combination with LHQW can be the first choice for the treatment of patients in critical condition [157] . In detail, Rhein, forsythoside A, forsythoside I, neochlorogenic acid and its isomers may be the effective active ingredients of LHQW against SARS-CoV-2 [158] . A retrospective analysis of JHQG treatment promotes the absorption of pneumonia permeate with a higher 7-day viral clearance rate compared with the control group [159] .…”
Section: Drugs Targeting Sars-cov-2-induced Inflammation In Host Cellsmentioning
confidence: 99%